Modern theoretical-methodological and economic-legal problems of implementing the concept of sustainable development of tourism and recreation in Ukraine - Ion Dubovich; Alla Anishchenko; Nadia Yurkiv; Yuliia Volkovska; Rostyslav Matsko; Oleh Rozhkovych; Mariana-Nadiia Dubovich; Oksana Pylypiak (Наукові праці Лісівничої академії наук України)
The tourism and recreation industry is one of the most promising and dynamic sectors of the economy and a key driver of socio-economic development.